TINDAK TUTUR EKSPRESIF PADA REAKSI VIDEO K-POP DI KANAL YOUTUBE TIM2ONE CHANDRALIOW - Arsyita Rahma Fitzgelard; Widya Ristiawati; Trea Inda Aprilova; Tiara Ananta Helma Lia Putri; Miftah Nugroho (Universitas Sebelas Maret, 2025)
The phenomenon of freedom of speech can occur in social media content, both text and video. In video content, for example, on the Youtube application. Freedom of speech and expression can be realized, one of which is through product review video content. One of the content creators who reviews music videos is Chandraliow. Tim2One is a Youtube channel built by Chandra Liow and his colleague, Tommy Lim. This study aims to describe the expressive speech acts found on Chandraliow's Tim2One Youtube channel. This type of research is qualitative research because it aims to understand what phenomena are experienced by the research subjects. The data collection method used in this study is the observation method. The data used in this study are the speech of Chandraliow and his second colleague which contain expressive speech acts. The data source for this study was taken from the music video reaction video on Chandraliow's Youtube channel. Data analysis in this study was carried out using the contextual analysis method. The results of the study found five types of expressive speech acts. The types of speech acts include, praise, thank, welcome, refute, and apologize.